Concentrations of organochlorine pesticides in umbilical cord blood and related lifestyle and dietary intake factors among pregnant women of the Huaihe River Basin in China. (July 2016) - Luo, Dan; Pu, Yabing; Tian, Haoyuan; Cheng, Juan; Zhou, Tingting; Tao, Yun; Yuan, Jing; Sun, Xin; Mei, Surong
Abstract: Organochlorine pesticides (OCPs), one of the persistent organic pollutants (POPs) with highly lipophilic properties, long half-lives, and persistence in the environment, are prevalent in the environment even though they have been banned for > 30 years. We aimed to investigate the current OCP exposure levels in cord blood from healthy pregnant women residing in the Huaihe River Basin, China, and examined the association between OCP levels and dietary habits and lifestyle factors. In this study, we measured the exposure levels of 17 OCPs in the umbilical cord blood from 999 healthy pregnant women; we also administered 1000 self-reported questionnaires regarding the general characteristics and dietary habits of those women. Our results showed that ρ, ρ′-DDE, ρ, ρ′-DDT, aldrin, dieldrin, and methoxychlor, which had higher measured concentrations (2.01 ± 1.89, 4.31 ± 5.68, 7.29 ± 8.74, 5.27 ± 7.65, and 0.98 ± 1.42 ng/mL, respectively) and detection frequencies (99.69%, 100.00%, 81.79%, 75.00%, and 74.49%, respectively), were the predominant OCPs in cord blood, and the higher levels of DDTs, aldrin, dieldrin, and methoxychlor were mainly due to recent use. In addition, most of the HCHs in cord blood were derived not only from historical use of technical HCH, but also from the additional use of lindane. In addition, we found that the education level of the pregnant women and monthly household income were positively correlated with OCP levels, particularly ρ, ρ′-DDE, aldrin, and dieldrin. Furthermore, the consumption of red meat (pork, beef, and lamb), fish, and bean products may be an important contributing factor to the increased concentrations of OCPs in cord blood, while the intake of poultry and pickles was negatively correlated with aldrin level. This study is the first to provide adequate data on current OCP exposure levels in cord blood from pregnant women in the Huaihe River Basin. Highlights: We measured the current exposure levels of 17 OCPs in the umbilical cord blood from 999 pregnant women in Huaihe River Basin of China for the first time. DDTs, aldrin, dieldrin and methoxychlor were the predominant OCPs. The levels of DDTs in our research were higher than those from previous studies conducted in other regions. The dietary intake has potential impacts on the OCP exposure levels.